2007
DOI: 10.1007/bf02980273
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory mechanisms of apigenin: inhibition of cyclooxygenase-2 expression, adhesion of monocytes to human umbilical vein endothelial cells, and expression of cellular adhesion molecules

Abstract: The aim of this study was to clarify the anti-inflammatory mechanism of apigenin. Apigenin inhibited the collagenase activity involved in rheumatoid arthritis (RA) and suppressed lipopolysaccharide (LPS)-induced nitric oxide (NO) production in a dose dependent manner in RAW 264.7 macrophage cells. Pretreatment with apigenin also attenuated LPS-induced cyclooxygenase-2 (COX-2) expression. In addition, apigenin profoundly reduced the tumor necrosis factor-alpha (TNF-alpha)-induced adhesion of monocytes to HUVEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 60 publications
3
83
2
1
Order By: Relevance
“…Apigenin profoundly blocked monocyte adhesion to the monolayer of human umbilical vein endothelial cells (HUVECs) by suppressing TNF-a-stimulated upregulation of VCAM-1, ICAM-1, and E-selectin mRNA expression. 47 Curcumin also decreased the intracellular ROS levels, phosphorylation of JNK, p38, and STAT3, and the expression of ICAM-1, MCP-1, IL-8, and lectin-like oxidized LDL receptor-1 (LOX-1) in TNF-a-stimulated HUVECs. 48,49 In the present study, pretreatment with SFN inhibited significantly NF-jB-induced IL-1, IL-6, IL8, and ICAM expressions, indicating that SFN has similar antiinflammatory and vasoprotective properties.…”
Section: Discussionmentioning
confidence: 92%
“…Apigenin profoundly blocked monocyte adhesion to the monolayer of human umbilical vein endothelial cells (HUVECs) by suppressing TNF-a-stimulated upregulation of VCAM-1, ICAM-1, and E-selectin mRNA expression. 47 Curcumin also decreased the intracellular ROS levels, phosphorylation of JNK, p38, and STAT3, and the expression of ICAM-1, MCP-1, IL-8, and lectin-like oxidized LDL receptor-1 (LOX-1) in TNF-a-stimulated HUVECs. 48,49 In the present study, pretreatment with SFN inhibited significantly NF-jB-induced IL-1, IL-6, IL8, and ICAM expressions, indicating that SFN has similar antiinflammatory and vasoprotective properties.…”
Section: Discussionmentioning
confidence: 92%
“…Inflammation-related genes such as adhesion cells contain binding sites for a number of important transcription factors, including NF-B [15,16] . Increase in adhesion cell gene expression is associated with inflammatory response which has been linked to the development of autoimmune disorders, coronary artery disease and cancer [17,18] . In this study, the results indicated that puerarin inhibited the expression of the protein and mRNA levels of ICAM-1, VCAM-1 and Eselectin in TNF-␣ -induced HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that stimulation of expression of endothelial NOS (eNOS) by apigenin occurs through phosphatidylinositol 3-kinase/Akt (PI3K/Akt) for Ca 2+ dependence . Moreover, the blockade of adhesion of monocytes and cyclooxygenase (COX)-2 expression in endothelial cells by apigenin has been reported (Lee et al, 2007). We have shown that apigenin strongly inhibits high glucose-and TNF--induced VCAM1 expression and the adhesion of U937 in human endothelial cells (Yamagata et al, 2010b).…”
Section: Vasorelaxant Effects Of Polyphenols On Endothelial Cellsmentioning
confidence: 75%